Hypoglossal nerve stimulator patient usage: Patterns and trends over time. Issue 5 (27th July 2022) - Morse, Elliot; Suurna, Maria
Abstract: Objective: Hypoglossal nerve stimulation (HNS) is an effective treatment for obstructive sleep apnea (OSA) patients intolerant of continuous positive airway pressure but is only effective if used regularly. Usage patterns have not been studied in detail. In this study, we aimed to characterize granular HNS usage patterns. Methods: Patients implanted by a single surgeon at an academic medical center from August 2016 to January 2021 were identified from a prospective database, which was merged with the Inspire Cloud usage database. Patient, OSA, and usage characteristics were summarized, and patient‐ and OSA‐related characteristics were associated with usage characteristics by Wilcoxon rank‐sum analyses. Usage trends over time were summarized in the overall cohort and stratified by initial usage. Results: Fifty patients were included. Median usage was 94% of nights (interquartile range [IQR]: 82%–98%) for 5.8 h per night (IQR: 4.9–6.4). Higher post‐operative apnea–hypopnea index predicted fewer nights used (92% [IQR: 82%–97%] vs. 96% [IQR: 91%–99%]). No other characteristics examined were significantly associated with usage. Median hours used per night decreased from 6.80 h (IQR: 5.32–7.94) on Day 1 to 5.76 (IQR: 1.81–7.13) on Day 361. This decrease was most pronounced in the quartile with the lowest initial usage. Conclusion: This study found that most patient and OSA characteristics were not associated with HNS usage, and that usage generally decreased over time. This decrease in usage over time was most pronounced in patients with the lowest initial usage. Further work should identify interventions to improve usage patterns to optimize clinical outcomes. Level of Evidence : 4. Abstract :